The Interactive Flipbook Local Wisdom: An Alternative to Support Students' Creative Thinking Skills - Hasanah; Sardianto Markos Siahaan; Masagus Mhd Tibrani (Universitas Pendidikan Ganesha, 2025)
Education in the digital era demands the availability of teaching materials that are interactive, contextual, and capable of enhancing student engagement and deep understanding. The integration of local wisdom values is a relevant approach to enrich the learning context and stimulate student creativity. However, classroom practices are still dominated by lecture methods and the use of less varied teaching materials, which do not fully support 21st-century learning needs. This study aims to analyze the needs of teachers and students regarding the development of interactive flipbooks for Natural and Social Sciences, specifically on the topic of regional superior products, as a medium to support elementary school students’ creative thinking skills. The study employed a survey method using questionnaires distributed via Google Forms to teachers and grade 5 students. Data were collected through needs-assessment questionnaires and analyzed qualitatively in a descriptive manner based on response tendencies, complemented by quantitative analysis of scores for each flipbook aspect. The results indicate that students have a very high level of need for all flipbook aspects, and teachers also report a very high need for this interactive learning medium. The study concludes that interactive, contextual digital flipbooks that support creative thinking are highly needed by both teachers and students. The findings imply the importance of developing innovative digital media that integrates local context, fosters creativity, and strengthens 21st-century learning design that adapts to technological advancements.